Legal Damages at Uncertain Causation - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
The legal notion of damages requires to compare the actual value of the creditor's assets with the hypothetical value that would have prevailed if the debtor had met his obligation. Moreover, values and causation may be uncertain. If nature's contribution is modelled as a random move then the interaction between debtor and nature can be described in normal form which, in turn, allows to capture causality and legal damages in a consistent way. In practice, such random moves of nature are rarely observable. Yet, statistical inference may reveal sufficient information to test for causation and to estimate legal damages on average over observable events as the present paper will establish.
urn:nbn:de:bvb:19-epub-13391-5
Keywords: K13; K12; D62; 330; estimating legal damages; liability for torts; liability for breach of contracts